Use (a + b)2 = a2 + 2ab + b2 to evaluate the following:

Use (a + b)2 = a2 + 2ab + b2 to evaluate the following:

(i) (101)2

(ii) (1003)2

(iii) (10.2)2

Answer :

(i) (101)2

It can be written as

= (100 + 1)2

Expanding using formula

= 1002 + 12 + 2 × 100 × 1

By further calculation

= 10000 + 1 + 200

= 10201

(ii) (1003)2

It can be written as

= (1000 + 3)2

Expanding using formula

= 10002 + 32 + 2 × 1000 × 3

By further calculation

= 1000000 + 9 + 6000

= 1006009

(iii) (10.2)2

It can be written as

= (10 + 0.2)2

Expanding using formula

= 102 + 0.22 + 2 × 10 × 0.2

By further calculation

= 100 + 0.04 + 4

= 104.04

More Solutions:

Leave a Comment